The absence or the pharmacological blockade of the aryl hydrocarbon receptor promotes neuroprotection in the hippocampus after an ischemic insult - Rolando Castañeda-Arellano; Lucia García-Lara; Quetzalli D. Angeles-López; Francisca Pérez-Severiano; Guillermo Elizondo-Azuela; Sergio H. Dueñas-Jimenez; Sirenia González-Pozos; Irene G. Aguilar-García; Jose Segovia (PLoS ONE, 2025)
The aryl hydrocarbon receptor (AhR) is a transcription factor that acts as a nuclear receptor mediating xenobiotic metabolism and environmental responses. Recent evidence suggests that the AhR is implicated in maintaining homeostasis or triggering pathological effects by modulating different physiological responses in the nervous system. However, the underlying mechanisms of the AhR-induced effects in the hippocampus remain unclear. Herein, we report a previously unknown role for the AhR in the pathogenesis of a transient global ischemic insult. Comparative analysis of the expression of HIF-1α, nNOS, iNOS, IL6, KAT II, and claudin 5 in the hippocampus of AhR +/+ and AhR -/- mice after bilateral common carotid artery occlusion revealed differential modulation. We report that AhR -/- mice significantly reduced the blood-brain barrier (BBB) dysfunction and neuronal death in hippocampus-CA1 caused by the ischemic insult, inducing neuroprotection. In addition, blocking the AhR with Resveratrol (a competitive antagonist) decreased neuronal degeneration and preserved the integrity of the BBB in the hippocampus associated with a neuroprotective effect. In summary, we showed that the AhR is an essential regulator for maintaining the BBB in the hippocampus and responds to inflammatory conditions and oxidative stress; further pharmacological targeting of AhR signaling may reduce the pathologic changes caused by an ischemic insult in the hippocampus.